New perspectives of hyperspectral imaging for clinical research. Issue 3 (June 2021) - Pallua, Johannes D; Brunner, Andrea; Zelger, Bernhard; Huck, Christian W; Schirmer, Michael; Laimer, Johannes; Putzer, David; Thaler, Martin; Zelger, Bettina
New developments in instrumentation and data analysis have further improved the perspectives of hyperspectral imaging in clinical use. Thus, hyperspectral imaging can be considered as "Next Generation Imaging" for future clinical research. As a contactless, non-invasive method with short process times of just a few seconds, it quantifies predefined substance classes. Results of hyperspectral imaging may support the detection of carcinomas and the classification of different tissue structures as well as the assessment of tissue blood flow. Taken together, this method combines the principle of spectroscopy with imaging using conventional visual cameras. Compared to other optical imaging methods, hyperspectral imaging also analyses deeper layers of tissue.